One Pot Optimized Synthesis of Cu-SAPO-34/Cordierite with HF and the Properties of NH3-SCR for NOx Removal - Qiao, Hui; Wang, Jiancheng; Gao, Zhijuan; Chen, Ying; Liu, Zhiqiang; Chang, Liping; Bao, Weiren (Asian Journal of Chemistry, 2014)
Cu-SAPO-34/cordierite catalysts, prepared via in situ hydrothermal synthesis technique with various HF content, of which the morphology and crystal structure were characterized by XRD and SEM, respectively. The activity of the catalysts prepared above for selective catalytic reduction (SCR) of NOx was evaluated with a fixed-bed reactor in simulated diesel vehicle exhaust. The results indicated that HF content played great roles on crystallization and catalytic properties of the samples. Loading amount and relative crystallinity of Cu-SAPO-34 were both increased along with the increasing n(HF)/n(Al2O3) ratio in the range of 0.01-0.03. The grain size became smaller and more uniform. The samples, crystallized for 24 h, have already showed a higher de-NOx activity and a stronger anti-aging property, over which the NOx conversion rate at the space velocity of 12 000 h-1 could reach higher than 95 % from 320 to 600 °C. As for the sample of n(HF)/n(Al2O3) = 0.03, NOx conversion rate could reach higher than 80 % from 380 to 560 °C at the space velocity of 36 000 h-1 and reached higher than 50 % from 460 to 580 °C after the aging treatment.